PENGARUH KARAKTERISTIK KARYA YB. MANGUNWIJAYA TERHADAP KARAKTER VISUAL PERMUKIMAN BANTARAN SUNGAI STUDI KASUS: KAMPUNG CODE UTARA, YOGYAKARTA - Ayu Wandira Puspitasari; Edward Endrianto Pandelaki; Bambang Setioko (TEKNIK, 2013)
Settlement of north Kampung Code which located on the riverbanks of Kali Code in Yogyakarta, has a diversevisual character, so that visually appear to be dynamic and irregular.Yusuf Bilyarta Mangunwijaya participatefully in shaping the visual character of the settlement of the north Kampung Code. The aim of this research is toknow the effect of characteristics design of YB. Mangunwijaya on the visual character of settlement riverbank inthe North Kampung Code.Quantitative-rasionalistic method was used in this research, based on the results of respondents answer inobservation the visual character of the north Kampung Code settlement. Testing using the test statistic basedfrom the answer of the respondents to the questionnaire. Quantitatively, the study was determined using outputrating statistics. Then the hypothesis testing was done through a linear regression analysis which serves toidentity that effect. Test conducted on the variable of characteristics design of Mangunwijaya consists of unitedwith nature, local, efficient, honest, detail and creative.The conclusions is a significant effect the characteristics design of YB. Mangunwijay on the visual character ofthe north Kampung Code was shown in this work.Correlation between respondents answer with theoryexplanation. Interpretation of this research was not every factor in forming the visual character can beunderstood properly by the observer.Key words: Visual Character, Characteristics Effect, The North Kampung Code, YB. Mangunwijaya